Initiating and potentiating role of platelets in tissue factor‐induced thrombin generation in the presence of plasma: subject‐dependent variation in thrombogram characteristics - Vanschoonbeek, K.; Feijge, M. A. H.; Van Kampen, R. J. W.; Kenis, H.; Hemker, H. C.; Giesen, P. L. A.; Heemskerk, J. W. M. (Journal of thrombosis and haemostasis, 2004)
The hemostatic activity of plasma is determined by platelet activation and coagulation, which processes are mutually stimulatory. We studied this interaction by measuring the cleavage of fluorescent thrombin substrate in platelet‐rich plasma (PRP), using the calibrated thrombogram method. In freshly isolated human plasma, thrombin formation triggered by tissue factor was fully dependent on the presence of platelets. It was abolished by annexin A5, indicating dependence on phosphatidylserine (PS) exposure at activated platelets. Comparison of plasmas from various subjects showed considerable interindividual variation in total amount of thrombin generation, regardless of whether platelets or PS‐containing phospholipids were present. Integrin αIIbβ3 antagonists and ADP receptor blockage, but not aspirin, decreased the rate of thrombin generation (thrombin peak level) and extended the time of onset. Platelet inhibition with cAMP‐elevating agents decreased the thrombin‐forming rate, but surprisingly shortened the onset time. Stimulation of platelets with agonists of Gi/q‐coupled receptors and, to a larger extent, with collagen or Ca2+‐ionophore increased the rate of thrombin generation and shortened its onset. In PRP from donors with low and high generation, platelet inhibitors and activators were similarly effective. Taken together, these results indicate that, in tissue factor‐triggered PRP, PS exposure on activated platelets regulates both onset and rate of thrombin generation. However, coagulant activity rather than platelet activation determines the total amount of thrombin formed, i.e. the endogenous thrombin potential. Thus, kinetics of thrombin generation in PRP are controlled by platelet inhibitors and agonists, but the process is restricted in amount by the subject‐dependent variation in coagulation.